PELAKSANAAN PERATURAN DAERAH KABUPATEN GIANYAR NOMOR 14 TAHUN 2012 TENTANG RETRIBUSI IZIN MENDIRIKAN BANGUNAN KHUSUSNYA TERHADAP SARANA BANGUNAN PARIWISATA ( STUDI PADA BADAN PELAYANAN DAN PERIZINAN TERPADU KABUPATEN GIANYAR) - Julian Pandie, Regil; Sudiartha, I Ketut; Sarna, Kadek (Kertha Negara : Journal Ilmu Hukum; Vol. 03, No. 01, Februari 2015)
This thesis entitled "Implementation of the Gianyar Regency Regulation No. 14 of 2012 on Building Permits Especially Against Means Tourism Building (Studies in Integrated Licensing Service Departement and Gianyar Regency), using empirical methods with legislation approach, fact approach , and analitical conceptional approach of law. The raised issue in this paper is how does the implementation of the Gianyar Regency Regulation No. 14 of 2012 by the Local Government in the Office of the Integrated Licensing Service Departement (BPPT) specialy in establshing the tourism facilities in the district if Gianyar and determine whether the factors that support and impede the implementation of the Regional Regulation No. 14 Year 2012. The conclusion is implementation of the local regulation can not be said operate effectively in view of the of the violations committed by the people/entrepreneurs about the activities of development without have permit and payment of the retribution in advance of Building Permit.
Keywords: Tourism Facilities, Retribution of Building Permit, Licensing